Inquiry-Based Physics Learning Module with Physics Education Technology Assistance to Improve High School Students' Critical Thinking Skills and Scientific Literacy - Kholida MS*, S. Ida; Tamam, Moh. Badri; Suprianto, Suprianto; Sumo, Maimon; Aprilita, Yeni Nur (Universitas Syiah Kuala, 2025)
Physics learning module is one of the teaching materials that can support the learning process so that one of the 21st century skills is achieved, critical thinking and scientific literacy. The current learning module has not fully trained these skills optimally. The purpose of this study is to develop a physics learning module based on integrated inquiry physics education technology (PhET) that is feasible (valid, practical, and effective) to improve critical thinking skills (CTS) and scientific literacy. The research method used is the development of Richey and Klein. The sample of this study was 70 students of class XI IPA of Public Senior High Schools in Pamekasan Regency. The research time was from July to August 2025 with a one group pretest posttest design research type. The research instruments were tests, implementation sheets, and expert validation sheets. The results showed that the developed learning module was very valid with an average value of 94%, Practical with a percentage of 94.8% implemented very practically. Effective with an N-gain score of 0.71 in the high category, the statistical test obtained sig (2-tiled) of 0.000, there is a significant difference in the pretest and posttest scores so that this module has a positive effect on improving CTS and scientific literacy. The conclusion based on the results of the study, the physics learning module developed is proven to be feasible to be applied in the learning process so that it has implications for improving CTS and scientific literacy